A szegedi lakóparkok társadalomföldrajzi vizsgálata - Hegedűs, Gábor (Közép-Európai Közlemények, 2009)
Modern gated communities first appeared in post-socialist European countries after the fall of Communism. During the transition to a market economy, socio-economic differences have increased immensely across the region and the development of gated communities has brought about a new form of residential segregation. Modern gated communities have no real antecedents in Hungary. Since the beginning of the 1990s, the spread of such communities (in Hungarian: ‘residential parks’) has been rapid in and around Budapest as well as in many other smaller cities. This study analyses the residential parks in – and around – Szeged. Based on our results, we concluded that the term ‘residential park’ is used too generally in Szeged, without consideration of the exact definitions applied in the Western world. Significant differences can be observed in the numbers and spatial distribution of gated neighbourhoods in the city. Residential parks occur in specific spatial patterns which appear to trigger local conflicts.